PASSCLAIM - Bone health and osteoporosis. - Prentice, A; Bonjour, J; Branca, F; Cooper, C; Flynn, A; Garabedian, M; Müller, D; Pannemans, D; Weber, P (2003)
BACKGROUND: The EC Concerted Action PASSCLAIM aims to produce a generic tool for assessing the scientific support for health-related claims for foods and food components. AIM: The task of the ITGB Working Group was to critically evaluate the categories of scientific evidence needed to support claims in relation to bone health and osteoporosis. METHODS: A framework was developed to describe the chain of evidence that is required to link the consumption of a food or food component to bone health outcomes. Techniques available for interrogating each link in the chain were identified and their strengths and weaknesses considered. This framework was used to determine intermediate markers of health outcome with respect to osteoporosis and to debate the level of evidence that would be required to substantiate claims of enhanced function or reduced disease risk. RESULTS: Use of this framework with osteoporotic fracture as the health endpoint resulted in the following judgements based on current knowledge: 1) bone mineral density (BMD) is an intermediate marker of bone health which, for people of any age and sex, can provide evidence of enhanced function; 2) for people over 50 years living in populations with a high incidence of fracture, BMD is an intermediate marker of osteoporotic fracture risk which can provide evidence of an increased probability of reduced disease risk; 3) because osteoporosis is defined as a state of increased fracture risk due to low bone mass and deterioration in bone microarchitecture, a claim of a definite reduction in osteoporosis or fracture risk requires similar substantiation to claims that fractures are prevented or treated, including clinical trials and animal studies; 4) data from lower in the chain of evidence, such as bone turnover and calcium bioavailability, are not, by themselves, sufficiently strongly related to bone health endpoints to provide evidence of enhanced function or reduced disease risk but can provide supporting information. CONCLUSIONS: In the light of existing scientific knowledge, a framework has been developed as a tool for considering the scientific support for claims relating to bone health and osteoporosis. To provide a working example, the framework has been used to assess the current position with osteoporotic fracture as the health endpoint. This experience will contribute to the formulation under PASSCLAIM of a generic tool for assessing the scientific support of health claims on foods.